Hubungan Perilaku Hidup Bersih Dan Sehat Terhadap Status Gizi Dan Status Kesehatan Anak Sekolah Dasar Negeri Angsau 2 Pelaihari - Norhasanah Norhasanah; Rosihan Anwar; Antias Eva Puspa Ningrum (HB PRESS, 2016)
The state of health is the health situation experienced by a person and the disease is a factor that is associated with the state of health of a person. The health of a person is said to be good if in a person's body is good nutrition and a maximum satisfied. Meanwhile, nutritional status is a state of the body because of food consumption and utilization of nutrients; health status is affected by the balance between intake and expenditure of nutrients for its use by the body. Nutritional needs that have a role in child development largely covers energy, carbohydrates and proteins, vitamins and minerals are known as elements of nutrition that influence growth and development of children. The nutritional needs of children can be met from the intake of food or beverages consumed at home and consumed outside the home, or often referred to as a street food. In addition to the consumption of food as a major factor affecting the health and nutritional status of a person, there are also other factors that can affect the health of children, behavior of living healthy and clean. Clean and healthy lifestyle behaviors, in essence, is the prevention of human behavior of various diseases. This study aims to determine the relationship of clean and healthy lifestyle behaviors to the health and nutritional status of children SDN Angsau 2 Pelaihari. This research used analytic investigation with the design of the cross section. The study population for all students SDN Angsau 2 samples Pelaihari. total sample of 60 respondents with two criteria for inclusion and exclusion. Based on the results of the statistical tests of Spearman correlation showed there was have association between clean and healthy lifestyle behaviors (p = 0.000) with children’s health status and nutritional status of children SDN Angsau 2 Pelaihari. Keywords : Clean and Healthy Lifestyle Behaviors, Nutritional Status, Children’s Health Status